State history, legal adaptability and financial development - Ang, James B. (2019)
A country’s cumulative experience with statehood influences its ability to consolidate power and create a capable bureaucracy. Longer statehood experience gives countries more time to adapt their laws to local needs, provided the legal system is adaptable. We find that, relative to British common law countries with the most flexible laws, German and Scandinavian civil law countries initially exhibit lower financial development. However, as their history of statehood grows longer, financial development improves in countries with adaptable laws such as the German and Scandinavian civil law countries. This is not the case in French civil law countries with more rigid legal systems. Our results mainly show no or at most a weakly negative effect of French civil law legal origin on financial development. We also explore how changes in stock market development over time, financial integration, and financial crisis are impacted by statehood experience, legal origins and their interaction.